Ale, Beer and Brewsters in England: Women's Work in a Changing World, 1300-1600 - Wallis, Faith (Labour / Le Travail, 1998)
The article reviews the book, "Ale, Beer and Brewsters in England: Women's Work in a Changing World, 1300-1600," by Judith M. Bennett.